Type a math problem

This site uses cookies for analytics, personalized content and ads. By continuing to browse this site, you agree to this use. Learn more

Type a math problem

Solve for y

y = -\frac{17}{4} = -4\frac{1}{4} = -4.25

$y=−417 =−441 =−4.25$

Steps for Solving Linear Equation

y = - \frac{ 1 }{ 4 } -4

$y=−41 −4$

Convert 4 to fraction \frac{16}{4}=4.

Convert $4$ to fraction $416 =4$.

y=-\frac{1}{4}-\frac{16}{4}

$y=−41 −416 $

Since -\frac{1}{4}=-0.25 and \frac{16}{4}=4 have the same denominator, subtract them by subtracting their numerators.

Since $−41 =−0.25$ and $416 =4$ have the same denominator, subtract them by subtracting their numerators.

y=\frac{-1-16}{4}

$y=4−1−16 $

Subtract 16 from -1 to get -17.

Subtract $16$ from $−1$ to get $−17$.

y=-\frac{17}{4}

$y=−417 $

Assign y

y≔-\frac{17}{4}

$y:=−417 $

Graph

Giving is as easy as 1, 2, 3

Get 1,000 points to donate to a school of your choice when you join Give With Bing

Share

Copy

Copied to clipboard

y=-\frac{1}{4}-\frac{16}{4}

Convert 4 to fraction \frac{16}{4}=4.

y=\frac{-1-16}{4}

Since -\frac{1}{4}=-0.25 and \frac{16}{4}=4 have the same denominator, subtract them by subtracting their numerators.

y=-\frac{17}{4}

Subtract 16 from -1 to get -17.

Examples

Quadratic equation

{ x } ^ { 2 } - 4 x - 5 = 0

$x_{2}−4x−5=0$

Trigonometry

4 \sin \theta \cos \theta = 2 \sin \theta

$4sinθcosθ=2sinθ$

Linear equation

y = 3x + 4

$y=3x+4$

Arithmetic

699 * 533

$699∗533$

Matrix

\left[ \begin{array} { l l } { 2 } & { 3 } \\ { 5 } & { 4 } \end{array} \right] \left[ \begin{array} { l l l } { 2 } & { 0 } & { 3 } \\ { - 1 } & { 1 } & { 5 } \end{array} \right]

$[25 34 ][2−1 01 35 ]$

Simultaneous equation

\left. \begin{cases} { 8x+2y = 46 } \\ { 7x+3y = 47 } \end{cases} \right.

${8x+2y=467x+3y=47 $

Differentiation

\frac { d } { d x } \frac { ( 3 x ^ { 2 } - 2 ) } { ( x - 5 ) }

$dxd (x−5)(3x_{2}−2) $

Integration

\int _ { 0 } ^ { 1 } x e ^ { - x ^ { 2 } } d x

$∫_{0}xe_{−x_{2}}dx$

Limits

\lim _{x \rightarrow-3} \frac{x^{2}-9}{x^{2}+2 x-3}

$x→−3lim x_{2}+2x−3x_{2}−9 $

Back to top